Cattle feedlot dust – laser diffraction analysis of size distribution and estimation of emissions from unpaved roads and wind erosion - Gonzales, Howell B. (Kansas State University, 2010)
Large cattle feedlots emit considerable amounts of particulate matter (PM), including TSP (total suspended particulates), PM[subscript]10 (PM with equivalent aerodynamic diameter of 10 μm or less), and PM[subscript]2.5 (PM with equivalent aerodynamic diameter of 2.5 μm or less). Particulate emissions result from pen surface disturbance by cattle hoof action, vehicle traffic on unpaved roads and alleyways, and wind erosion. Research is needed to determine concentrations of various size fractions, size distribution, and emission rates from various sources in feedlots. This research was conducted to measure particle size distribution using laser diffraction method and estimate emissions from unpaved roads and wind erosion. Particle size distribution and concentrations of PM[subscript]10 and PM[subscript]2.5 at a commercial cattle feedlot in Kansas (Feedlot 1) were measured over a 2-yr period. The feedlot had a capacity of 30,000 head and total pen area of 50 ha and was equipped with a sprinkler system for dust control. Collocated low-volume samplers for TSP, PM[subscript]10, and PM[subscript]2.5 were used to measure concentrations of TSP, PM[subscript]10, and PM[subscript]2.5 at the upwind and downwind edges of the feedlot. Dust samples that were collected by TSP samplers were analyzed with a laser diffraction analyzer to determine particle size distribution. Particle size distribution at the downwind edge of the feedlot was also measured with micro-orifice uniform deposit impactor (MOUDI). The laser diffraction method and MOUDI did not differ significantly in mean geometric mean diameter (13.7 vs. 13.0 μm) but differed in mean geometric standard deviation (2.9 vs. 2.3). From laser diffraction and TSP data, PM[subscript]10 and PM[subscript]2.5 concentrations were also calculated and were not significantly different from those measured by low-volume PM[subscript]10 and PM[subscript]2.5 samplers (122 vs. 131 μg/m[superscript]3 for PM[subscript]10; 26 vs. 35 μg/m[superscript]3 for PM[subscript]2.5). Both PM[subscript]10 and PM[subscript]2.5 fractions decreased as pen surface moisture contents increased, while the PM[subscript]2.5/PM[subscript]10 ratio did not change much with pen surface moisture content. Published emission models were used to estimate PM[subscript]10 emissions from unpaved roads and wind erosion at Feedlot 1 and another nearby feedlot (Feedlot 2). Feedlot 2 had a capacity of 30,000 head, total pen surface area of 59 ha, and used water trucks for dust control. Estimated PM[subscript]10 emissions from unpaved roads and wind erosion were less than 20% of total PM[subscript]10 emissions obtained from inverse dispersion modeling. Further research is needed to establish the applicability of published emission estimation models for cattle feedlots.
Keywords: PM emissions from cattle feedlots; Particle size distribution; Laser diffraction; Wind erosion; Unpaved roads; Engineering, Agricultural (0539); Engineering, Environmental (0775)